Nano tracks in fullerene film by dense electronic excitations - Kumar P.; Avasthi D.K.; Ghatak J.; Satyam P.V.; Prakash R.; Kumar A. (My University, 2025)
In the present work, we investigate the formation of nano tracks by cluster and mono-atomic ion beams in the fullerene (C 60 ) thin films by High Resolution Transmission Electron Microscopy (HRTEM). The fullerene films on carbon coated grids were irradiated by 30 MeV C 60 cluster beam and 120 MeV Au mono-atomic beams at normal and grazing angle to the incident ion beams. The studies show that the cluster beam creates latent tracks of an average diameter of around 20 nm. The formation of large size nano tracks by cluster beam is attributed to the deposition of large electronic energy density as compared to mono-atomic beams. © 2014 Elsevier B.V. All rights reserved.